Free convection in a partially heated wavy porous cavity filled with a nanofluid under the effects of Brownian diffusion and thermophoresis; Applied Thermal Engineering; Vol. 113 - Sheremet M. A. Mikhail Aleksandrovich (2017, 2017)
Title screen